Теорія чотириполюсників і схема заміщення трансформатора - Придубков, П.Я.; Хоменко, І.В. (Електротехніка і електромеханіка, 2011)
Not enough high efficiency of the use of structures of the known charts of substitution of linear transformer, which is explored by the theory of quadripoles, allowing to define coefficients forms of record of equalizations of quadripole, is exposed, to find complex resistances vivid chart of his substitution, being and chart of substitution of transformer, is synonymous the proper to the electromagnetic processes.